Evolution mechanism of microscopic pores in pavement concrete under multi-field coupling. (10th June 2018) - Guo, Yinchuan; Chen, Zhihui; Qin, Xiao; Shen, Aiqin; Zhou, Shengbo; Lyu, Zhenghua
Highlights: The evolution of micropore structure is investigated under multi-field coupling. The deterioration rules of micropore are discussed dynamically at the micro-scale. The quantitative analysis is realized by the optical method and fractal theory. The evolution mechanism of micropore in seasonally frozen regions is proposed. Abstract: To explore micropore deterioration and its mechanism in pavement concrete in seasonally frozen regions, multi-field fatigue tests were conducted. The mercury intrusion method, the optical method and scanning electron microscopy (SEM) were used to quantitatively characterize the pore structure of specimens in multi-field coupling conditions in terms of properties such as the porosity, mean pore size (MPS), pore size distribution (PSD), stomatal distance coefficient (SDC) and box fractal dimension (BFD). Next, the dynamic deterioration rules of micropores under different coupling levels were discussed at the micro-scale. The results show that the coupling effect significantly accelerates the deterioration of pavement concrete, while the stratified feature of micropores is weakened and the complexity of micropores is increased as more pores experience deformation, splitting and nucleation. Under the action of a single load, the porosity shows a 'initiating-closing-splitting' trend, while the MPS reveals a 'compressing-expanding' trend, and the BFD first increases and then decreases with the increase in loading cycles. The crystal expansion stress initiated by the fatigue load and freeze-thaw coupling effect weakens the ability to disperse internal stress, leading to the pore structure parameters showing a tendency of monotonous rapid deterioration after the turning point, and the concrete reveals fatigue failure with larger porosity and SDC compared to that of a single field. Under the triple-field coupling, a large shrinkage stress is generated rapidly; the system cannot be relieved through structural deformation in time, causing MPS to increase, the pore distribution complexity (BFD) to decrease, and more micropores to nucleate.